2014
DOI: 10.1037/a0032592
|View full text |Cite
|
Sign up to set email alerts
|

Do media portrayals of obesity influence support for weight-related medical policy?

Abstract: The findings indicate that simply eliminating stigmatizing media portrayals of obesity may help reduce bias.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 16 publications
1
46
0
Order By: Relevance
“…These findings suggest that the formation, maintenance, and expression of implicit anti-fat attitudes may be at least somewhat sensitive to common media depictions of people with obesity. Recent experimental studies have found that viewing images of people with obesity engaged in stereotypical stigmatizing activities increased explicit bias toward obese people compared to viewing positive images [911]. The present study suggests that implicit attitudes may be strengthened by visual media portrayals of obese individuals engaging in stereotypical behaviors (e.g., overeating/watching TV).…”
Section: Discussionsupporting
confidence: 44%
See 1 more Smart Citation
“…These findings suggest that the formation, maintenance, and expression of implicit anti-fat attitudes may be at least somewhat sensitive to common media depictions of people with obesity. Recent experimental studies have found that viewing images of people with obesity engaged in stereotypical stigmatizing activities increased explicit bias toward obese people compared to viewing positive images [911]. The present study suggests that implicit attitudes may be strengthened by visual media portrayals of obese individuals engaging in stereotypical behaviors (e.g., overeating/watching TV).…”
Section: Discussionsupporting
confidence: 44%
“…Recent experimental studies have found that viewing images of people with obesity engaged in stereotypical stigmatizing activities increased explicit bias toward obese people compared to viewing positive images [9, 10]. Similarly, in experimental research on media portrayals of obesity and weight-related medical policy, participants who view non-stigmatizing images were less supportive of a policy to deny obese women fertility treatment than participants who viewed stigmatizing images [11]. However, an unanswered question in implicit weight bias research remains: is weight bias stronger when obese and thin people are shown engaging in stereotype consistent behaviors (e.g., obese—watching TV/eating junk food; thin—exercising/eating healthy) as opposed to the converse?…”
Section: Implicit Weight Bias and Stereotype Incongruent Imagesmentioning
confidence: 99%
“…Weight discrimination is the unjust treatment of individuals because of their weight . Individuals with obesity experience discrimination from educators , employers, health professionals , the media and even from friends and family . Although weight discrimination is pervasive in our society, few efforts have been made to address it .…”
Section: Introductionmentioning
confidence: 99%
“…The ways in which obesity is portrayed in the news media can shape how people considered obese are understood by the general public (12,13,18). Because of the increasing presence of social media, weight loss and other health-related information are frequently sought through interactive forums such as Facebook, Twitter and Yahoo Answers (19)(20)(21)(22).…”
Section: What This Study Adds?mentioning
confidence: 99%